An Analysis of Labour Adjustment Costs in Unionized Economies - Leonor Modesto; Jonathan P. Thomas (Institute for the Study of Labor (IZA), 2000)
In this paper we conduct a theoretical analysis of the implications of a union which can exploit the existence of firm labour adjustment costs. We consider a model involving a large number of identical firms facing a single, economy-wide union. We solve (i) for the Markov perfect equilibria with no commitment, under the assumption that the union chooses wages each period and firms react by choosing employment, and (ii) for the commitment equilibria where the union can precommit to the entire (infinite) sequence of wages. We conclude that the speed of adjustment of employment, that is higher in the nocommitment case, decreases with adjustment costs in both models. Moreover adjustment costs affect the long run values of employment and wages only in the no-commitment case, i.e., the higher the relevance of adjustment costs the higher the wage and therefore the smaller the level of employment in the long run. Commitment on the part of the union leads to lower wages, and moreover is beneficial to firms as well as to the union. Given that the union would like to commit to a lower path of wages we consider whether reputation building is desirable.
Keywords: J32; J23; J65; J51; 330; Unions; labour adjustment costs; Markov perfect equilibria; Arbeitsmarkttheorie; Gewerkschaftlicher Organisationsgrad; Lohnpolitik; Arbeitsnachfrage; Anpassungskosten; Beschäftigungseffekt; Lohn; Spieltheorie; Theorie